Konstruksi Media terhadap Tujuan Program Makan Bergizi Gratis (MBG) dalam Liputan Berita Daring: Fokus pada Aspek yang Ditonjolkan - Ksatriawan Zaenuddin; Anirwan (Research and Development Agency Ministry of Home Affairs, 2026)
This study analyzes the media construction of the Free Nutritious Meal (MBG) program’s objectives in online news coverage through the lens of agenda-setting theory. It emphasizes three main dimensions—object salience, attribute salience, and actor salience—to understand how the media shapes issue priorities, policy interpretations, and the dominant voices in public discourse. Using a descriptive qualitative case study design, 150 articles from Kompas.com, Detik.com, and Tempo.co were analyzed via NVivo 15. The results indicate that coverage is dominated by objectives related to nutritional intake and stunting reduction (42.01%); while other objectives, such as food security and economic growth, receive significantly less attention. At the attribute level, the media frames the MBG program primarily as a nutrition-based intervention for vulnerable groups, marginalizing other development dimensions. At the actor level, discourse is dominated by state entities—specifically the National Nutrition Agency (BGN) and various ministries—reflecting a state-centered agenda. These findings highlight the need to position the MBG program as a cross-sectoral policy and strengthen inclusive public communication.